Volatility of the international commodity market and its relationship with inflation in Peru - Gomero Gonzales, Nicko Alberto (2022)
Objective: To determine the relation between the volatility of the prices of international commodities and the inflation rate, and the collateral effects on the Gross Domestic Product (GDP) and the generation of employment. Method: The approach was quantitative, and the level was correlational. Given the normality of the data, by the non-parametric Kolmogorov-Smirnov (K-S) contrast, which p-value result in all cases was greater than 5%, the Pearson test was used to determine the degree of relation between the variables under analysis. The used data was obtained from official sources only, such as the Central Reserve Bank of Peru, the International Monetary Fund, the Food and Agriculture Organization of the United Nations, and Petroperu, covering the period from January 2021 to June 2022, including the phase that involved the global crisis. Results: The volatility of cereal and fuel prices exerted moderate pressure on inflation, the effect of which did not translate into negative changes in GDP and employment; on the contrary, these macroeconomic variables managed to advance despite the volatility of the inflation rate. Conclusion: The volatility of the prices of international commodities, due to the supply shock, generated some influence on inflation; however, the economic growth figures and a labor market with job openings are maintained.